Halal investment strategies and earnings enhancement model for Malaysia SMEs: a bibliometric analysis - Nik Mat, Nik Hziman; Akbar, Mohamed Aslam; Ramdzan Ali, Al Amirul Eimer; Mohd Thas Thaker, Mohamed Asmy; Mohd Noor, Noor Azlan (Quantum Academic Publisher Enterprise, 2025)
This paper conducts a comprehensive systematic bibliometric meta-analysis to map the intellectual landscape and research trends on halal business investment strategies and earnings enhancement for Small and Medium Enterprises (SMEs) in Malaysia. It aims to identify key themes, gaps, and future directions for optimizing SME performance through moral and Shari’ah-compliant financial practices. The study further proposes the foundation for a Halal Investment Strategies and Earnings Enhancement Model (HISEM), designed to strengthen sustainable growth and competitiveness in Malaysia’s halal economy. Close to a thousand English-language publications from the Scopus database (2009–2025) were screened, of which 365 relevant studies were selected through systematic filtering and manual validation. The data were analyzed using RStudio (Biblioshiny), VOSviewer, and Microsoft Excel to generate bibliometric maps and trend analyses across authorship, institutional affiliations, and thematic clusters. The analysis reveals Malaysia’s dominant contribution to global halal research and identifies key thematic clusters like halal entrepreneurship, halal certification and business performance, supply chain and risk management, halal tourism and lifestyle, and technological innovation in halal logistics. Despite increasing publication volume, there remains a limited theoretical synthesis linking halal investment frameworks directly to SME profitability. This study proposes the conceptualization of the HISEM to bridge that gap and guide empirical applications. The dataset is confined to English-language studies indexed in Scopus with a Malaysian focus, primarily within the fields of economics, business, and finance. Future research could expand to non-indexed and multilingual sources for broader insights.This paper is among the first to integrate bibliometric analysis with a model-oriented approach for halal investment strategies and earnings enhancement. It contributes a foundational framework for developing SME strategies and policymaking in the halal economy, providing both academic enrichment and practical guidance for sustainable economic advancement